An exploratory study of the factors contributing to school dropout among girls in Temeke district of Dar es Salaam, Tanzania - Rwechungura, Jeniphar Kokusima (Department of Social Development, 2014)
The purpose of this study was to explore the factors contributing to school dropout among girls in Temeke district of Dar es Salaam, Tanzania. A qualitative exploratory study approach was adopted by using a semi-structured interview schedule of face?to-face interviews. The study involved a sample of 20 girls aged between 12 and 23 years using purposive and snowball sampling techniques. The findings revealed that participants dropped out of school for various reasons, including lack of financial support, loss of parents, parents being sick, poor performance, pregnancy, early marriage, and rape. In addition, the findings revealed that although young girls had dropped out of school, they still aspired to pursuing further education and acquiring different skills in order for them to achieve their goals. The girls indicated that the major obstacle to achieving their dreams was a lack of sufficient money to start their own small business and pay for training and transport costs, as most vocational centres are located far from their communities. Due to these daily challenges, these girls desired more support from their communities. Most of the girls shared the concern that no one had ever shown an interest in the specific factors causing them to stop their schooling. Based on the findings of the study, the major recommendations are for the government to provide subsidies to parents who cannot afford to support their children?s education. In addition, the government in collaboration with other stakeholders should establish skills training centres within communities so as to impart skills to young girls to enable them either to establish their own businesses or, alternatively, to find employment. Furthermore, those who intend to start their own business should be supported by access to funding and business development support services. The study recommends that non-governmental organisations (NGOs) working in partnership with the local authorities, schools and communities should intensify their interventions aimed at addressing social issues such as early marriages and pregnancy in Temeke district. NGOs should also publicise their activities and programmes to ensure that young girls know about the different options available to them. The study also recommends that girls should be actively focused on their education and be supported to form local networks as a means of them working together to realise their dreams.